Réponses

2013-09-05T00:19:00+02:00
1)   \frac{1}{n} - \frac{1}{n + 1} = \frac{n + 1}{n (n + 1)} - \frac{n}{n (n + 1)}
 
                        = \frac{n + 1 - n}{n (n + 1)}

                        = \frac{1}{n (n + 1)}


2)   Par conséquent :

       \frac{1}{1 \times 2} +   \frac{1}{2 \times 3} +  \dots +  \frac{1}{n (n + 1)} =  (\frac{1}{1} - \frac{1}{2}) + (\frac{1}{2} - \frac{1}{3}) + \dots + (\frac{1}{n} - \frac{1}{n + 1})

                                                         = \frac{1}{1} - \frac{1}{n + 1}

                                                         = 1  - \frac{1}{n + 1}